Use Of Information And Communication Technology In Islamic Educational Learning Evaluation Activities - Moh. Sahlan (FALASIFA : Jurnal Studi Keislaman, 2023)
In general, this article aims to provide an understanding to teachers or managers of Islamic education institutions in utilizing Information and Communication Technology (ICT) in learning evaluation activities, specifically the use of ICT. First, in terms of preparing the items using the programHot Potatoes andWondershare Quiz Creator which has many varied menus such as making multiple choice questions, short answers, matching and others;Second, carrying out tests using a computer with online, semi-online, or offline mechanisms. Computer-based exams or tests have a number of advantages such as practicality, but they also have drawbacks in their use such as a machine that suddenly crashes;Third, item analysis activities, can usemicrosoft excel, SPSS, and Anates;Fourth, Utilization of ICT to report student learning outcomes with the Dapodik Version 2017C application.